Sistem Penilaian Kinerja untuk Pengembangan SDM pada PT SIT Global Systems dengan Metode AHP - Setiawati, Anjani; Primawati, Alusyanti; Akhirina, Tri Yani (LPPM STT Terpadu Nurul Fikri, 2025)
An objective and structured employee performance assessment is critical in supporting human resource (HR) development in the company. This study aims to design a decision support system (DSS) with the Analytical Hierarchy Process (AHP) method to assist PT SIT Global Systems in conducting comprehensive employee performance assessments. The AHP method was chosen because it produces consistent calculations based on the weighting of predetermined criteria and sub-criteria, thereby reducing subjectivity in the assessment process. This system is built using the NetBeans application with the Java programming language and uses MySQL as a database to manage and store all employee assessment data. This application allows users to manage employee data, calculate employee final grades, and generate assessment reports. With this system, the assessment result can be used as a basis for decision-making related to further HR development. This system is expected to support management in improving the company’s HR performance.